Green tea epigallocatechin gallate suppresses 3T3-L1 cell growth via microRNA-143/MAPK7 pathways. Issue 18 (September 2022) - Chen, Chia-Pei; Su, Tsung-Chen; Yang, Meei-Ju; Chen, Wen-Ting; Siao, An-Ci; Huang, Ling-Ru; Lin, Yen-Yue; Kuo, Yow-Chii; Chung, Jia-Fang; Cheng, Ching-Feng; Ku, Hui-Chen; Kao, Yung-Hsi
Green tea epigallocatechin gallate (EGCG) and microRNA (miRNA) molecules modulate obesity. Nevertheless, it is still unknown whether EGCG modulates fat cell growth via miRNA-related signaling. In this study, white preadipocytes were used to examine whether the antimitogenic effect of EGCG on fat cells is regulated by the miR-143/MAPK7 pathway. We showed that EGCG upregulated the levels of miR-143, but not miR-155, in 3T3-L1 preadipocytes. Moreover, EGCG downregulated MAPK7 mRNA and protein levels time- and dose-dependently. MAPK7 expression increased during 3T3-L1 cell proliferation. miR-143 overexpression in the absence of EGCG mimicked the effects of EGCG to suppress preadipocyte growth and MAPK7 expression, whereas knockdown of miR-143 antagonized the EGCG-altered levels of miR-143, MAPK7, and pERK1/2 and reversed the EGCG-inhibited cell growth. These findings suggest that EGCG inhibits 3T3-L1 cell growth via miR-143/MAPK7 pathway.